h - Haller, Armin; Huang, Guangyan; Huang, Zhisheng; Paik, Hye-young.; Sheng, Quan Z.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the revised selected papers of the combined workshops on Web Information Systems Engineering, WISE 2011 and WISE 2012, held in Sydney, Australia, in October 2011 and in Paphos, Cyprus, in November 2012. The seven workshops of WISE 2011-2012 have reported the recent developments and advances in the contemporary topics in the related fields of: Advanced Reasoning Technology for e-Science (ART 2012), Cloud-Enabled Business Process Management (CeBPM 2012), Engineering in the Semantic Enterprise (ESE 2012), Social Web Analysis for Trend Detection (SoWeTrend 2012), Big Data and Cloud (BDC 2012), Personalization in Cloud and Service Computing (PC-S 2011), and User-Focused Service Engineering, Consumption and Aggregation (USECA 2011).
Advanced Reasoning Technology for e-Science (ART 2012) -- Cloud-Enabled Business Process Management (CeBPM 2012) -- Engineering in the Semantic Enterprise (ESE 2012) -- Social Web Analysis for Trend Detection (SoWeTrend 2012) -- Big Data and Cloud (BDC 2012) -- Personalization in Cloud and Service Computing (PC-S 2011) -- User-Focused Service Engineering, Consumption and Aggregation (USECA 2011).
Keywords: Computer science; Information storage and retrieval systems; Information systems; Management information systems; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Business Information Systems; Computer Appl. in Administrative Data Processing